2002
DOI: 10.1089/105072502753451904
|View full text |Cite
|
Sign up to set email alerts
|

Selective Uptake ofp-Borophenylalanine by Undifferentiated Thyroid Carcinoma for Boron Neutron Capture Therapy

Abstract: Undifferentiated thyroid carcinoma (UTC) lacks an effective treatment. Boron neutron capture therapy (BNCT) is based on the selective uptake of 10B-boronated compounds by some tumors, followed by irradiation with an appropriate neutron beam. The radioactive boron originated (11B) decays releasing 7Li, gamma rays and alpha particles, and these latter will destroy the tumor. In order to explore the possibility of applying BNCT to UTC we have studied the biodistribution of BPA. In in vitro studies, the uptake of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Analytical and internal standard lines (in nm) were as follows: B: 249.677 and Y: 371.029. Matrix-matched standard solutions containing the internal standard elements and boron between 0.05 and 0.75 mg/mL were employed for daily calibration [33][34][35]. An internal measurement control was also used, with each certain number of samples adding a sample of known concentration (QC).…”
Section: Determination Of Intracellular Boron By Inductively Coupled mentioning
confidence: 99%
“…Analytical and internal standard lines (in nm) were as follows: B: 249.677 and Y: 371.029. Matrix-matched standard solutions containing the internal standard elements and boron between 0.05 and 0.75 mg/mL were employed for daily calibration [33][34][35]. An internal measurement control was also used, with each certain number of samples adding a sample of known concentration (QC).…”
Section: Determination Of Intracellular Boron By Inductively Coupled mentioning
confidence: 99%
“…Nonetheless, a compact accelerator has been developed as an alternative to a nuclear reactor, and it can be installed in a hospital, thus facilitating the easy application of BNCT [ 76 ]. Dagrosa et al [ 77 79 ] reported the application of BNCT for undifferentiated TC in vitro and in an in vivo mouse model. However, the clinical advantages of BNCT in TC management remain unknown.…”
Section: Clinical Application Of Lat1-targeting Agentsmentioning
confidence: 99%
“…The boron concentration of the medium in each flask at the end of incubation was checked by inductively coupled plasma optical emission spectroscopy (Perkin-Elmer, Norwalk, CT) as described elsewhere (13).…”
Section: Experimental Designmentioning
confidence: 99%